The Effect of Internal Audit Effectiveness: Accountability, Objectivity and Auditor Ethics - Mega Puspa Ningrum; Cris Kuntadi (Sean Institute, 2024)
Internal audit effectiveness is a measure of the success or failure of the internal audit system in achieving predetermined goals through various possible choices. This article provides an overview of the factors that influence Internal Audit Effectiveness, namely: The purpose of writing this article is to develop hypotheses about the influence between variables that will be used in further research. The results of this literature review article are: 1) Accountability affects the Effectiveness of Internal Audit; 2) Objectivity affects the Effectiveness of Internal Audit; and 3) Auditor Ethics affect the Effectiveness of Internal Audit.